Copper Bracelets and Magnetic Wrist Straps for Rheumatoid Arthritis – Analgesic and Anti-Inflammatory Effects: A Randomised Double-Blind Placebo Controlled Crossover Trial - Richmond, Stewart J.; Gunadasa, Shalmini; Bland, Martin; MacPherson, Hugh (PLOS ONE, 2013)
Background Folklore remedies for pain and inflammation in rheumatoid arthritis include the application of magnets and copper to the skin. Despite the popular use of devices containing magnets or copper for this purpose, little research has been conducted to evaluate the efficacy of such treatments. Objective To investigate whether the practice of wearing magnetic wrists straps, or copper bracelets, offers any specific therapeutic benefit for patients with rheumatoid arthritis. Design Randomised double-blind placebo-controlled crossover trial. Methods 70 patients, aged 33 to 79 years and predominantly female (n = 52), with painful rheumatoid arthritis were recruited from general practices within Yorkshire. Participants were randomly allocated to wear four devices in a different order. Devices tested were: a standard (1502 to 2365 gauss) magnetic wrist strap, a demagnetised (<20 gauss) wrist strap, an attenuated (250 to 350 gauss) magnetic wrist strap, and a copper bracelet. Devices were each worn for five weeks, with treatment phases being separated by one week wash-out periods. The primary outcome measured was pain using a 100 mm visual analogue scale. Secondary pain measures were the McGill Pain Questionnaire and tender joint count. Inflammation was assessed using C-reactive protein and plasma viscosity blood tests and by swollen joint count. Physical function was assessed using the Health Assessment Questionnaire (Disability Index). Disease activity and medication use was also measured. Results 65 participants provided complete self-report outcome data for all devices, four participants provided partial data. Analysis of treatment outcomes did not reveal any statistically significant differences (P>0.05) between the four devices in terms of their effects on pain, inflammation, physical function, disease activity, or medication use. Conclusions Wearing a magnetic wrist strap or a copper bracelet did not appear to have any meaningful therapeutic effect, beyond that of a placebo, for alleviating symptoms and combating disease activity in rheumatoid arthritis. Trial Registration Controlled-Trials.com ISRCTN51459023 ISRCTN51459023.